An Analysis of Logistic Cost Structure in Corn Commodity Supply Chain (Zea Mays L) in East Java Using Activity Based Costing (ABC) Method - Heryanto, A Y (Emerging Advances in Integrated Technology, 2025)
East Java is Indonesia’s biggest corn producer in 2022, with a percentage of 26,24. The El Niño phenomenon of 2023 caused a decrease in corn production in Indonesia. El Nino phenomenon in non-farming land can add logistic costs, especially in procurement. The goal of the logistic cost structure analysis is to determine the proportion of logistic costs. This research was conducted in three regencies in East Java, a representative of the corn producer centre. A total of 98 respondents were included in the study. The research sample was selected based on convenience sampling and snowball sampling. The Activity Based Costing (ABC) method calculates the logistic-cost structure. The structural analysis of logistic costs used descriptive statistics. The analysis of the logistic cost structure showed that the most significant proportion of logistic cost was procurement activity, with a percentage of 63,09%. The activity at the farmers’ tier with the most significant cost proportion was procurement activity, with a percentage of 69,73%. Transportation was the activity with the most considerable logistic cost proportion in the collector trader and large trader tiers, with proportions amounting to 52,31% and 83,01%. The right supply chain strategy for corn commodities in East Java was push-based.